Rwanda : Request for Extensions of the Standby Credit Facility Arrangement and the Policy Support Instrument-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Rwanda's Request for Extensions of the Standby Credit Facility (SCF) Arrangement and the Policy Support Instrument. The SCF is aimed at complementing the authorities' efforts to address growing external imbalances. Both near and medium term adjustment policies to position Rwanda's external position on a sustainable basis are part of an overall strategy to support growth, support poverty reduction and improve the country's resilience to future uncertainties in the global economy. Program performance is on track. All continuous and end-June 2017 quantitative assessment/performance criteria were met, as were almost all indicative targets. Most structural benchmarks have already been met or are in progress. The IMF staff supports the authorities' request for the extensions through January 31, 2018.